Dos inscripciones funerarias inéditas de Aptera, Creta (Minerva, 2019)
The author of the paper presents two new funerary inscriptions of the Helenistic age from Aptera in Crete. They are inscriptions recently found during the archaelogical excavations carried out by the Greek archaeologist V. Niniou in the place of the city of the same name.
Keywords: Funerary inscriptions; Hellenistic age; Aptera; Creta